The effect of board of directors’ characteristics on anti-money laundering: Evidence from banks sector (International Journal of Management and Sustainability, 2024)
This study aims to investigate how board composition affects banks' efforts to combat money laundering. It was an applied research study using a descriptive and correlational design. All banks operate in the Arab world. We used screening procedures to select a sample of banks. The findings indicate the inclusion of board members with expertise in compliance, law, or finance has a favorable effect on financial institutions' AML initiatives. Board members who have experience in the financial sector or who have specific knowledge of anti-money laundering laws improve the results of anti-money laundering efforts, thereby avoiding fines for their companies. The Board of Director’s knowledge of anti-money laundering legislation, its ability to ensure the bank’s adherence to national and international anti-money laundering laws, and its flexibility in responding to regulatory modifications positively impact the commitment to anti-money laundering. The Board of Directors is the controller of the institution and therefore has the main role in combating money laundering. A board of directors committed to combating money laundering keeps the entire organization compliant and avoids the risks of money laundering.